2017
DOI: 10.1103/physrevb.96.024421
|View full text |Cite
|
Sign up to set email alerts
|

Magnonic band structure in a Co/Pd stripe domain system investigated by Brillouin light scattering and micromagnetic simulations

Abstract: By combining Brillouin Light Scattering and micromagnetic simulations we studied the spin-wave dynamics of a Co/Pd thin film multilayer, features a stripe domain structure at remanence. The periodic up and down domains are separated by cork-screw type domain walls. The existence of these domains causes a scattering of the otherwise bulk and surface spin-wave modes, which form mode families, similar to a one dimensional magnonic crystal. The dispersion relation and mode profiles of spin waves are measured for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 70 publications
4
60
0
Order By: Relevance
“…In these systems, magnetocrystalline and surface anisotropies are typically opposing the magnetostatic selfinteraction, causing the occurrence of heterogeneous microscopic magnetic states in order to minimize their total energy [17,[19][20][21]. The resulting nanoscale magnetic textures have attracted significant interest due to their technological potential [22][23][24][25][26][27][28], as well as for their structural complexity [29][30][31][32]. In particular magnetic bubbles, which correspond to cylindrically shaped domains extending throughout the total thickness [33], were intensively studied largely motivated by their potential for applications in solid state storage [34,35].…”
Section: Iintroductionmentioning
confidence: 99%
“…In these systems, magnetocrystalline and surface anisotropies are typically opposing the magnetostatic selfinteraction, causing the occurrence of heterogeneous microscopic magnetic states in order to minimize their total energy [17,[19][20][21]. The resulting nanoscale magnetic textures have attracted significant interest due to their technological potential [22][23][24][25][26][27][28], as well as for their structural complexity [29][30][31][32]. In particular magnetic bubbles, which correspond to cylindrically shaped domains extending throughout the total thickness [33], were intensively studied largely motivated by their potential for applications in solid state storage [34,35].…”
Section: Iintroductionmentioning
confidence: 99%
“…Notable examples are magnonic waveguides and spin-wave filters exploiting domain walls or different types of nanoscale spin textures [68][69][70][71][72][73]. Moreover, recent studies showed that stripe domains can be used to control spin-wave propagation, by changing the relative orientation between the spin-wave wave vector and the domains axis [74,75], suggesting the possibility to exploit stripe domains to realize reconfigurable spin-wave devices.…”
Section: Introductionmentioning
confidence: 99%
“…This so‐called spin rectification effect (SRE), which is due to nonlinear coupling between an oscillating current and an oscillating resistance in magnetic structures, provides a novel technique for the study of magnetization dynamics by electrical detection. Due to its high sensitivity and feasibility, the SRE has been widely employed to study ferromagnetic resonance (FMR), spin wave resonance, and domain‐wall resonance in different ferromagnetic materials. Furthermore, the SRE has become an essential tool for studying novel spin dynamics including spin torque (ST), spin pumping (SP), and spin Hall effect (SHE) …”
Section: Introductionmentioning
confidence: 99%